A parametric study of dredged marine soils as passive geosorbent for escherichia coli removal in leachate - Anuar, Nurasiah Mira (2022)
A high demand for dredging in the Malaysian water has resulted in a large amount of geowaste name dredged marine soils (DMS). The material are discarded in designated disposal sites on- and off-shore. A large number of studies in reusing this material within recent years demonstrate the importance of finding better management of DMS after the dredging process. The effective use of DMS as an adsorbent to remove chemical contaminants from leachate as potential alternatives to landfill liner has received widespread attention because of the environmentally friendly nature of clay material. A potential reuse area yet to be explored is the utilization of DMS to remove Escherichia coli (E. coli) from leachate. Effect of DMS geotechnical properties is a key point laid behind understanding passive removal of E. coli in leachate. Therefore by simulating landfill site, the efficiency of DMS as a geosorbent was studied. This study explored the effect of pH, soil particle size, salinity and temperature on E. coli removal from leachate. Geosorbent samples from various depths of each reactor were also retrieved and assessed to profile the spatial distribution of the E. coli. This study showed that the hydraulic conductivity of DMS fell within the acceptance range for liner material. The output count of E. coli was lower after 35 days of exposure to a high salinity level. E. coli removed by lower pH were antagonistic as their presence in the leachate was decreased. Also, the finer particle size required a longer time to adsorb the E. coli due to the soils’ porosity. The measured result in a higher temperature degree supported the idea that E. coli growth in landfill leachate was suppressed by the increment of the temperature. Concurrently a high number of E. coli was counted in the DMS with less than 0.0001% of E. coli was found in the effluent. The findings from this study concluded that DMS has the potential to be reused as a geosorbent to retain E. coli in leachate.